DFT study on the molecular mechanism of the [4 + 2] cycloaddition between thiobenzophenone and arylalkenes via radical cations - Heredia, Luis Domingo (2009)
The mechanistic aspects of the radical cationic version of the [4 + 2] cycloaddition between thiobenzophenone 1 and three aryl-substituted alkenes 2a-c have been studied using DFT methods at the UB3LYP/6-31G level of theory. In the ground state, the Diels-Alder reaction follows an asynchronous concerted mechanism; the large activation energy associated with bond formation prevents this process. After generation of the radical cation (RC), formation of a molecular complex (MC) between 1 and 2a-c initiates a stepwise mechanism, with attack of the sulfur atom of 1 to the aryl-conjugated position of 2a-c. Subsequent ring closure is the rate-determining step of these cycloadditions. Methoxy or dimethylamino substitution at the aryl group, while stabilizing the corresponding RC, results in a less exothermic formation of MC and a significant increase of the cycloaddition barrier.